2021
DOI: 10.3389/fpubh.2021.707078
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Risk Factors for Small-for-Gestational-Age Newborns in Mexico: Analysis of a Nationwide Representative Cohort

Abstract: Background: Small for gestational age (SGA) is a key contributor to premature deaths and long-term complications in life. Improved characterization of maternal risk factors associated with this adverse outcome is needed to inform the development of interventions, track progress, and reduce the disease burden. This study aimed to identify socioeconomic, demographic, and clinical factors associated with SGA in Mexico.Methods: We analyzed administrative data from 1,841,477 singletons collected by the National Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Every year, pseudonymised and validated datasets of live births and deaths are published online separately 11,12 . Given that most live births and deaths occurred in healthcare facilities, national coverage has been estimated to reach more than 90.0% of the target population, but this percentage varies at the subnational level 17,18 …”
Section: Methodsmentioning
confidence: 99%
“…Every year, pseudonymised and validated datasets of live births and deaths are published online separately 11,12 . Given that most live births and deaths occurred in healthcare facilities, national coverage has been estimated to reach more than 90.0% of the target population, but this percentage varies at the subnational level 17,18 …”
Section: Methodsmentioning
confidence: 99%
“…Downloaded from Open access these infants to higher risk of insulin resistance, obesity, dyslipidaemia and hypertension in adulthood. [4][5][6] SGA infants often experience early-life catch-up growth (CUG). CUG is described as the upward crossing of centiles observed in infants born low birth, 7 and also defined as an increase in Z score of >0.67 between twotime points.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…smoking, drug consumption, or exposure to toxic substances [13,14]), inadequate prenatal care or socioeconomic risk factors [15]. The latter includes maternal educational attainment [11][12][16][17][18][19][20], maternal age [12,[21][22][23], ethnicity [11,[24][25][26] and marital status [20]. Social inequalities in health thus appear in the very earliest stages of life [27][28][29].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Birth weight can be also related to ethnicity. Based on the UK Millennium Cohort Study (MCS), [21] Indian, Pakistani, Bangladeshi, Black Caribbean and Black African infants were more likely to be low birthweight compared to White infants. Burris and Hacker [37] reported that in the USA black infants are disproportionately more likely to be born with LBW.…”
Section: Plos Onementioning
confidence: 99%